Sonotetranychus angiopenis n.sp. (Acari:Tetranychidae) from Bauhinia sp. (Fabaceae) in northwestern São Paulo State, Brazil - Feres, Reinaldo J.F.; Flechtmann, Carlos H.W. (Taylor & Francis, 1995)
A new spider mite, Sonotetranychus angiopenis n.sp., collected from Bauhinia sp. (Fabaceae) is described from northwestern São Paulo State, Brazil. This is the first record for this genus in South America. © 1995 Taylor and Francis Group, LLC.